Design of Fixed Assets Depreciation Accounting Information System with the Straight Line Method Using Microsoft Visual Studio 2010 at PT Sagala Group - Siti Salwa Julia Septiani; Wulan Nurdiah; Resmi Ranti Rosalina (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
For more than one accounting period, a business will likely make use of the physical assets that make up its fixed assets, such as those used in manufacturing, transportation, office space, and other structures. Investment in fixed assets must be carefully considered because to its high value, relatively extended usage, and status as the company's primary instrument for producing money. The value of fixed assets depreciates over time, and depreciation is the process through which that decline in value is accounted for. The straight-line depreciation approach is used by many businesses since it results in consistent expenses over time periods, regardless of changes in productivity or other factors. Therefore, it is essential that owned assets be properly managed so that businesses and individuals can continue to reap the rewards of their existence. However, this is not the case with PT Sagala Group still using Microsoft Excel to record its assets and calculate depreciation. Inaccuracies in fixed asset depreciation calculations, lags in recognizing physical data, and inadequate oversight of firm assets are only some of the issues discovered in the absence of supplementary software. In light of this issue, the authors reach the conclusion that a unified system for handling the various aspects of depreciating fixed assets should be created, with Microsoft Visual Studio 2010 and Microsoft Access 2010 serving as the respective database development and management tools. In the long run, having this system in place should make business operations easier.